Analisis Pengaruh Indeks Pembangunan Manusia, Angkatan Kerja, dan Belanja Modal Daerah terhadap Peningkatan PDRB Provinsi di Indonesia - Muhammad Nur Wicaksono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Economic growthinanareacan be seenfrom theGross Regional Domestic Product (GRDP)inthe area. Until now,Indonesiahas agrowthratewhichis lesssogood. This tends tobe causedbymanyfactors. Factorsthat includethe HumanDevelopmentIndex, the labor force, andcapital expenditureareas. Inthis studywillexaminethe influenceofthe three factors aboveto the increase inGross Regional Domestic Product (GRDP). This studyusessecondary datawithpanel dataregression. The dataused is the23 provincesinIndonesia in2008-2012. The model usedisRandom EffectModel(REM). The regression resultsindicate apositive significant effectonindexManPembngunanandlabor forcetoincreaseGross Regional Domestic Product (GRDP). Whilethe effect ofthecapital expendituretoGDPis not significantimprovementdespite havinga positiveimpact. Keywords :Gross RegionalDomestic Product, Human Deveopment Indeks, labor force, regional capital expenditure